A taxonomy of indicators for non-communicable diseases: agreement, definition, and contextual description using diabetes as a case study - Carinci, Fabrizio; Poljičanin, Tamara; Cunningham, Scott; Fava, Stephen; Štotl, Iztok; Lepiksone, Jana; Nicholson, Nicholas; Massi Benedetti, Massimo; Klazinga, Niek (Frontiers in Public Health, 2025)
BackgroundThe Collaborative Health Information European Framework (CHIEF) is an initiative led by the Joint Research Centre (JRC) of the European Commission to enable a sustainable data collection and production of indicators to monitor and evaluate best practices for people with NCDs.ObjectivesWe aimed to support international assessment and comparability of NCD indicators through a taxonomy of NCD indicators, a core set of measurable diabetes indicators and high-level policy recommendations.Materials and methodsThe study is an expert review run by the multidisciplinary expert group “CHIEF-diabetes.dwg” between 2022 and 2024. The group convened on several remote and in-presence meetings. A common set of key references were identified to underpin collective discussions and agree on the fundamental criteria for the selection of indicators. An iterative process was followed to reach agreement and release final recommendations.ResultsA taxonomy of NCD indicators and relevant stakeholders was identified to guide the selection process. A core set of diabetes indicators was agreed, including: diabetes incidence and prevalence rate, retinopathy prevalence rate, major lower extremity amputation incidence rate, blindness rate and rate of end stage renal disease. Measurement issues across chronic diseases and data collection were included in recommendations to the EU.DiscussionThe taxonomies and core set of diabetes indicators identified by the expert group may be used as a proof of concept of a collaborative European framework. The expert group recommended: (a) to determine the purpose of NCD indicators in advance; (b) to prioritise actionable indicators for the high-level governance of chronic diseases; (c) to align with existing standardisation processes; (d) to build on the experience of existing registries; and (e) to align with current efforts to strengthen the EU data infrastructure.ConclusionThe expert group delivered general guidance on criteria and principles for the selection of NCD indicators, using diabetes as a case study. The core set of six diabetes indicators can be used as a field-test for future reporting initiatives. In this context, disease registries can provide the high-quality data needed to compute reliable indicators. Targeted projects are needed to design a cohesive health information system of NCD indicators.